El Niño episodes coincide with California moray Gymnothorax mordax settlement around Santa Catalina Island, California. Issue 4 (31st January 2017) - Higgins, B. A.; Pearson, D.; Mehta, R. S.
Abstract : The hypothesis that El Niño events influence the settlement patterns of the California moray Gymnothorax mordax is tested. The pelagic larval duration (PLD) of larval G. mordax is unknown, but studies on leptocephalus of related species suggest that larvae are long‐lived, up to 2 years. Gymnothorax mordax, an elusive predatory species and the only muraenid off the coast of California, is considered abundant in the waters around Catalina Island. Thirty‐three individuals were collected from Two Harbors, Catalina Island, and otoliths were taken to provide estimates of their age. Settlement year for each individual was backcalculated using estimated age from otolith measurements. These ages were then cross referenced with the Oceanic Niño Index (ONI) developed by the National Oceanographic and Atmospheric Administration (NOAA) to correlate estimated age of settlement with known El Niño years. Of the 33 individuals collected, 30 settled at Catalina Island during El Niño years. The oldest individual in the data‐set was 22 years old, placing G. mordax as one of the longer‐lived predatory fishes in the system. The present study represents the first account of wild G. mordax ages and suggests that El Niño events have an important role in driving the settlement of recruits towards the northern edge of their range.